Analisis Kekuatan Struktur Rangka Alat Uji Konduktivitas Termal Berbasis Metode Elemen Hingga - Firman Firman; Yolli Fernanda (Lembaga Yasin AlSys, 2026)
Although thermal conductivity test apparatuses have been widely used to characterize the heat transfer properties of materials, studies that specifically address the strength of their supporting frame structures remain limited. In testing practice, the frame of the apparatus is subjected not only to thermal loads but also to mechanical loads arising from the weight of components and clamping forces, so an inadequate structure may experience excessive deformation, reduce measurement accuracy, and shorten the service life of the apparatus. This study aimed to analyze the strength and stiffness of the frame structure of a thermal conductivity test apparatus based on the Comparative Cut-Bar Method using the Finite Element Method (FEM). A quantitative approach was employed through numerical simulation using ANSYS Workbench 2025. The frame geometry was designed in SolidWorks with low-carbon steel AISI 1010 as the material, followed by static structural analysis with fixed support boundary conditions and loading variations of 135 N, 145 N, and 155 N, representing the operating conditions of the test apparatus. The analyzed parameters included total deformation and equivalent stress. The simulation results showed that maximum deformation occurred at the central support seat of the frame, with values ranging from 0.000000089501 mm to 0.00000010276 mm, which are very small and do not affect the stability or functionality of the apparatus. The maximum equivalent stress ranged from 0.00583 MPa to 0.0066975 MPa, far below the elastic limit of AISI 1010 steel of 305 MPa. These findings indicate that the frame structure of the thermal conductivity test apparatus has very good strength and stiffness and is safe to use under the analyzed operating conditions. This study provides a basis for structural evaluation and a design reference for the frame of thermal conductivity test apparatuses to support measurement reliability and long-term use.